34.6: Design and Application Analysis of Hybrid Thin‐film Transistor Structures. (4th October 2019) - Li, Lingxia; Tan, Li; Li, Xiaohu; Zhu, Rundong; Cai, Kaimin; Li, Ting; Jiang, Wei
Abstract : This paper studies the development of hybrid thin‐film transistors in recent years based on patents and articles from companies in the display field. Including the comparison of the design concept of the hybrid thin‐film transistor by Apple and LG, and the improvement of the possible problems raised by the company. Finally, the application prospects and development trends of hybrid thin‐film transistors are analyzed.